Development of a dip coating tool for thin layer growers based on the Raspberry Pi 3 - Inandita Mardhiyah; - Yohandri (Department of Physics – Universitas Negeri Padang UNP, 2020)
v>Low cost and precise is a concern in developing instruments for thin-film manufacturing. In this paper, alow-cost dip-coating instrument based on Raspberry pi will be presented. In this work, Raspberry Pi 3 wasadopted as a microcontroller for digital data processing. In addition, this tool is also equipped with a user-friendly interface system that is easy to operate by the user. An addition, the Python programming language is also adopted in the development of programming on the Raspberry Pi 3. Furthermore, the Raspberry Pi is alsoneeded to build an interface on the tool with the Qt designer framework. The results of device configurationssuch as withdraw speed and immersion time can be stored in the data logger system that has been developed inthis equipment. The performance and characteristics of the equipment have been tested and produce excellentcharacteristics and performance that meet the criteria for the production of thin film. Based on the results, a dipcoating based on Raspberry pi can be applied to the production of thin film in nanomaterial technology.